Effect of Leaching Time on Dissolution of Gold Metal (Au) in Gold Ore Deposits by Hydrometallurgical Process - Nurliah Jafar; Sitti Ratmi Nurhawaisyah; Firdaus F; Muhammad Idris Juradi; Andi Artiningsih; Mubdiana Arifin; Suriyanto Bakri (Jurnal Geomine, 2022)
One of Indonesia’s potential gold ore deposits is found in the Bolaang Mongondow area of North Sulawesi Province. This research is one of the initial studies conducted to determine the metal content of gold in ore deposits based on the results of Au extraction using aqua regia. It is known that several operating parameters determine the success rate of the leaching process. One of these parameters is the leaching time. The leaching time ranges used in the study were 5, 10, 20, 60, and 120 minutes. Based on the variation of the leaching time applied to the leaching process, it will also be known how much mass of dissolved Au metal is. The leached filtrate obtained was then analyzed for its concentration using AAS (Atomic Absorption Spectrometry) instrument. The AAS data were then processed using x and y curves to obtain the optimum leaching time, and the mass of dissolved Au metal was obtained using the equation. The results showed that the optimal time for the hydrometallurgical process in gold ore deposits was 120 minutes with an Au concentration of 1.67 mg/L.